Evaluation of Nguni cattle performance from communal property associations and private ownership types across three ecological zones of Mpumalanga province, South Africa - Sambo, J M; Tada, O; Chitura, T; Mararakanye, N (Asian Journal of Agriculture and Rural Development, 2023)
Nguni cattle in South Africa are diminishing at the expense of exotic breeds and crossbreeds. Therefore, the Industrial Development Corporation and Mpumalanga Province Department of Agriculture adopted the Nguni cattle conservation project. Herds of 30 heifers and a bull were allocated to 34 communal property associations (CPAs) and 40 private farms. This study aimed to evaluate growth and reproductive performance across three ecological zones and two ownership patterns. Nine CPAs and nine private farms were sampled. Age at first calving, conception, calving, and weaning rates were determined from production records, while calf birth and weaning weights were digitally measured. Data was analyzed using two-way analysis of variance (ANOVA) with Tukey’s honestly significant difference (HSD) used for mean separation. Significant differences were observed across ecological zones for age at first calving, weaning rate, and birth and weaning weights (p < 0.05). Concerning age at first calving, the Midveld ecological zone performed best (24 months) for both ownership types compared to the Highveld (28.09 months private, 26.00 CPA) and Lowveld (28.35 months for both ownership types). Highveld performed higher on birth weight (25.35 kg) and weaning rate for private (93%) and CPA (80%). Lower birth weights were observed in both ownership types in Midveld (22.17 kg). The Lowveld zone had a higher birth weight (26.80 kg) in CPA. Higher weaning weights were observed in private ownership of Highveld (190.16 kg) and the lowest (160.39 kg) in the Midveld zone. CPAs in Highveld had higher weaning weights (187.55kg) than in Midveld (167.50 kg). The results suggest that Nguni cattle respond differently in the various ecological zones of Mpumalanga Province.